The restrictions of the freedom of information during the Covid-19 pandemic - Калітенко, Оксана Михайлівна; Калітенко, О. М.; Калитенко, Оксана Михайловна; Kalitenko, Oksana M.; Анікіна, Галина Володимирівна; Анікіна, Г. В.; Аникина, Галина Владимировна; Anikina, Halyna V.; Anikina, Galyna; Спасова, Катерина Іванівна; Спасова, К. І.; Спасова, Екатерина Ивановна; et al. (Universidad del Zulia, 2021)
The article is devoted to the study of the issues of restrictions on the freedom of information that has arisen under the impact of the novel coronavirus outbreak. Another goal of the paper is identifying ways to protect such rights or to indicate which amendments to the law might be of use. The research methodology is based on general and special scientific methods, in particular: analytical, comparative-legal, systemic, and structural. The structure of the work includes: the review of international and Ukrainian legislation related to the freedom of information; the possibilities of its restriction; possible ways to enabling safe and secure management of the freedom of information during the coronacrisis. An analysis of international experience was carried out, as well as aspects of the protection of civil liberties such as freedom of speech, the right of peaceful assembly, etc. Several problematic issues were identified. Although, the general results of the study can be interpreted as alarming trends in the field of human rights and civil liberties. Particularly, it is multiple violations of the freedom of information all around the world under quarantine restrictions.

Стаття присвячена дослідженню питань обмеження свободи інформації, що виникли під впливом спалаху нового коронавірусу. Іншою метою статті є визначення способів захисту таких прав або визначення того, які зміни до закону можуть бути корисними. Методологія дослідження базується на загальнонаукових і спеціально-наукових методах, зокрема: аналітичному, порівняльно-правовому, системному та структурному. Структура роботи включає: огляд міжнародного та українського законодавства щодо свободи інформації; можливості його обмеження; можливі шляхи забезпечення безпечного та надійного управління свободою інформації під час коронакризи. Було проведено аналіз міжнародного досвіду, а також аспектів захисту громадянських свобод, таких як свобода слова, право на мирні зібрання тощо. Визначено декілька проблемних питань. Хоча загальні результати дослідження можна інтерпретувати як тривожні тенденції у сфері прав людини та громадянських свобод. Зокрема, це багаторазові порушення свободи інформації в усьому світі під карантинними обмеженнями.
Kalitenko O. The restrictions of the freedom of information during the Covid-19 pandemic / O. Kalitenko, G. Anikina, E. Spasova, O. Shahaka // Cuestiones Politicas. - Vol. 39. - Iss. 70. - Universidad del Zulia, 2021. - Р. 426-445.
Keywords: freedom of information; freedom of speech; Covid-19; restrictions; human rights; свобода інформації; свобода слова; Covid-19; обмеження; права людини; Research Subject Categories::LAW/JURISPRUDENCE